Bayesian binomial assurance tests for system reliability using component data. - Hamada, M.S (Journal of Quality Technology)
This paper illustrates the development of Bayesian assurance test plans for system reliability assuming that binomial data will be collected on the system and the previous information is available from component testing. The posterior consumer's and producer's risks are used as the criteria for developing the test plan. Using the previous component information reduces the number of tests needed to achieve the same levels of risk. The proposed methodology is illustrated with two examples.